The meaning of sedentary behavior among older adults: a phenomenological hermeneutic study - Joakim Niklasson; Cecilia Fagerström; Patrick Bergman; Terese Lindberg; Sofia Backåberg (BMC, 2023)
Abstract Background A sedentary lifestyle has implications for health and well-being. For healthy ageing, it is recommended to interrupt prolonged sitting; however, little is known about the meaning of sedentary behavior among older adults. The aim of this study was to understand the meaning of sedentary behavior among older adults with initial support from community care. Methods A phenomenological hermeneutics approach was used, and individual interviews were conducted with sixteen older adults aged 70 to 97 years, by phone and face to face. The older adults lived in ordinary housing in southern Sweden and received initial support from community care. Results The interviews yielded three key themes: Being sedentary is an unnatural part of life, having an ageing body means unwanted frailty, and having a sedentary lifestyle is based on conscious choices. Conclusion Being sedentary means having a lack of physical activity and social interactions, resulting in wanting to be more physically active than sometimes possible. Clinical practitioners should bear in mind that becoming more sedentary is inevitable with an ageing body, but that older adults may have an innate desire to be as physically active as possible. A lifelong exposure to physical activity, the possibility of well-being found in sedentary activities and the impact of social networks should not be overlooked when creating clinical interventions to break unhealthy sedentary behavior among older adults. To increase the understanding of sedentary behavior among older adults, future research could focus on the impact of physical impairment on sedentary behavior and the relationship between sedentary behavior and physical activity throughout life.